Relationship between adiposity and heart rate recovery following an exercise stress test in obese older women - Cristiane Rocha da Silva; Dahan Cunha Nascimento; Luana Claudia Dias Bicalho; Ramires Alsamir Tibana; Bruno Saraiva; Jeffrey M Willardson; Jonato Prestes; Guilherme Borges Pereira (Universidade Federal de Santa Catarina, 2017)
The aim of the present study was to compare differences in heart rate (HR) response during and following exercise in obese older women with different percent body fat levels. Ninety older, obese women aged 60-87 years participated in the study, were categorized, and enrolled to one of two groups based on a lower percent body fat (LPBF ≤ 41.10 %) or higher percent body fat (HPBF > 41.10 %) as measured by dual-energy x-ray absorptiometry. The peak HR during exercise and in the first and second minutes of recovery period were compared between groups. The HPBF group presented a lower peak HR during exercise (p = 0.001) and an impaired HR recovery (p = 0.001) when compared to LPBF group. The present study demonstrated that older women who were in exceedingly obese level have an impaired heart rate response during exercise and in the recovery period, indicating possible autonomic dysfunction.